Radon concentration in residential areas of Bann Pang Fan, Chiang Mai province, Thailand - S. Sriburee (2020)
© 2019 Published under licence by IOP Publishing Ltd. This study examined the radon concentration in residential areas of Bann Pang Fan, Chiang Mai Province, Thailand. Measurement was carried out for radon concentration in 59 residences from February to June 2017 using plastic alpha track detectors or CR-39 placed in wooden and cement bedrooms and living rooms. It was found that the radon concentration was 26-322 Bq•m-3, with an average at 53.94±29.43 Bq•m-3. In the bedroom, the concentration was 28-143 Bq•m-3, while in the living room it was 26-322 Bq•m-3. When calculating the annual effective dose of the residences, it was found to be at 0.21-1.71 mSv/year. The annual effective dose of 52.54% for the residences was higher than 1 mSv/year, as recommended by UNSCEAR.